Acute Adhesive Obstruction at The Present Stage: Possibilities of Laparoscopy in Diagnosis and Treatment (Literature Review) (Texas Journal of Medical Science, 2022)
Acute adhesive intestinal obstruction is one of the most urgent and finally unresolved problems of modern abdominal surgery. This is characterized by an increasing number of this complication, high mortality, and many difficulties in its diagnosis and treatment. The paper outlines the etiology, epidemiology, differential diagnosis of acute adhesive obstruction, as well as the modern principles of diagnosis and surgical treatment of this disease.